2016
DOI: 10.1002/ijc.30381
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐gated sodium channel Nav1.7 promotes gastric cancer progression through MACC1‐mediated upregulation of NHE1

Abstract: Voltage-gated sodium channels (VGSCs), which are aberrantly expressed in several human cancers, affect cancer cell behavior; however, their role in gastric cancer (GC) and the link between these channels and tumorigenic signaling remain unclear. The aims of this study were to determine the clinicopathological significance and role of the VGSC Nav 1.7 in GC progression and to investigate the associated mechanisms. Here, we report that the SCN9A gene encoding Nav 1.7 was the most abundantly expressed VGSC subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 48 publications
3
70
0
1
Order By: Relevance
“…Sixth, HIF-1α increases transcription of lactate transporters, including monocarboxylate transporter 4 and NHE1 exchanger present on tumor cell membranes [68, 69] to cope with intracellular lactic acidosis [56]. Elevation of these transporters is associated with poor prognosis in lung and stomach cancer [70, 71]. HIF-1α also buffers pH by upregulating carbonic anhydrase 9 and 12, whose protein products catalyze hydration of CO 2 into bicarbonate.…”
Section: Hif Upregulation In Cancer: Consequencesmentioning
confidence: 99%
“…Sixth, HIF-1α increases transcription of lactate transporters, including monocarboxylate transporter 4 and NHE1 exchanger present on tumor cell membranes [68, 69] to cope with intracellular lactic acidosis [56]. Elevation of these transporters is associated with poor prognosis in lung and stomach cancer [70, 71]. HIF-1α also buffers pH by upregulating carbonic anhydrase 9 and 12, whose protein products catalyze hydration of CO 2 into bicarbonate.…”
Section: Hif Upregulation In Cancer: Consequencesmentioning
confidence: 99%
“…• Gastric cancer Paehler Vor der Nolte et al, 2017 Xue et al, 2011Czepán et al, 2012Liu et al, 2008He et al, 2010;Nagata et al, 2011;Hosogi et al, 2012;Xia et al, 2016;Xie et al, 2017 NHE1 Intestine…”
Section: The Role Of Nhe1 In Barrett's Esophagus and Its Progressionunclassified
“…The study results demonstrated that Na v 1.7 controls GC cell invasion and proliferation by MACC1-mediated upregulation of NHE1. Therapies that specifically target Na v 1.7 might successfully impede GC progression [73]. However, there have been no other reports on VGSCs in GC.…”
Section: Voltage-gated Sodium Channelsmentioning
confidence: 99%
“…Our study showed the VGSC inhibitor tetrodotoxin (TTX) decreased MACC1 and NHE1 expressions, which decreased the extracellular pH and increased the intracellular pH. This affected the GC cell proliferation and invasion in vitro [73]. However, we did not use TTX in the experiments on mice, which should be done in the future.…”
Section: Pharmacological Targeting Of Ion Channels and Aqps For Cancementioning
confidence: 99%